CHALLENGES WITHIN THE FINANCIAL-ACCOUNTING ACTIVITY IN THE CONTEXT OF COVID-19 - Mariana GURĂU; Maria Zenovia GRIGORE; Mihaela Ioana GURĂU (Challenges of the Knowledge Society)
The period of the COVID-19 pandemic brought many economic, social and environmental challenges. In the financial-accounting sector, the situation of uncertainty, including remote work, has generated and continues to generate various problems for companies and their employees. One of these is the temporary inability of employees to carry out their activity even within the financial-accounting activity. Another challenge that many companies have faced has been the adoption of online commerce as a method of maintaining the business during the pandemic. This form of trade also meant different work for the financial-accounting departments, which had to adapt to the new style of trade, which also involves new financial-accounting rules and regulations. In this paper we analyze the challenges to which the financial-accounting activity have been subjected as a result of the numerous measures of fiscal and commercial nature, but also some long-term benefits of these measures.